Cell-Based Therapy Of Human Adipose- Derived Mesenchymal Stem Cell Expressing Angiopoietin-1 In An Experimental Model Of Airway Inflammation - Halim, Nur Shuhaidatul Sarmiza Abdul (2018)
Cell-based therapy of mesenchymal stem cells (MSCs) has been shown to enhance the endogenous repair process by increasing the limited regenerative capacity of the lung in chronic lung disorders as well as following injury. However, the underlying cellular and molecular mechanisms of MSCs to enhance airway regeneration and repair are remain unclear. This study was aimed to investigate the effect of delivering human adipose-derived MSCs (hAD-MSCs) alone and in combination with vasculoprotective factor, the ANGPT1, by aerosol technique in a rabbit model of asthma related-airway inflammation. Given the anti-inflammatory, anti-permeability, and endothelial-protective characteristics of ANGPT1, we hypothesise that, combining MSCs with ANGPT1 offers promise in the treatment of airway inflammation. Transfection of hAD-MSCs with ANGPT1 was performed using microporation technique. For in vivo study, the rabbit were sensitised with combination of ovalbumin (Ova) and alum injection and further challenged with Ova inhalation to induce asthma-related airway inflammation. The MSCs and MSC-pANGPT1 were aerosolised directly into the airway using the MicroSprayer® Aerosolizer 48 h after injury. Histopathological assessments of the airway inflammation along with local inflammatory responses were quantitatively measured at three days after cell delivery. To investigate the functional effect of MSCs on airway regeneration and repair, an indirect in vitro co-culture model of injured airway epithelium explant with MSCs was developed. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis was performed to determine the factors secreted by MSCs and their involvement in epithelium regeneration and repair was evaluated by histopathological assessment.